Meningioma in a 20-Month-Old Boy - Jung, Yeon-Seong; Song, Young-Jin (Journal of Korean Neurosurgical Society, 2012)
A 20-month-old boy presented with a intraparenchymal mass in the right frontoparietal area manifesting as complex partial seizure, secondary generalization and left hemiparesis. Magnetic resonance images (MRI) of the brain showed inhomogeneously enhancing mass in the right frontoparietal area which has irregular margin and perilesional edema. Based on the radiological findings, a preoperative diagnosis was an intraaxial tumor, such as pilocytic astrocytoma or dysembryoplastic neuroepithelial tumor. The patient underwent a surgery including frontal craniotomy. The tumor had a partially extreme adherence to the surrounding brain tissue but it showed no dural attachment. Gross-total resection of the tumor was achieved. Postoperative follow-up computed tomography scans showed no residual tumor. The pathological findings confirmed the tumor as a WHO grade I meningioma, transitional type. Nine months after the surgery, follow-up brain MRI showed no recurrence of the tumor, porencephaly in site where the tumor was resected; the patient's symptoms had fully recovered. We report the case of a meningioma in a 20-month-old boy.